Implementation Implementation Of The Kahoot Aplication In Aqidah Akhlak Learning At Islamic Primary School: Implementasi Aplikasi Kahoot Dalam Pembelajaran Aqidah Akhlak Di Madrasah Ibtidaiyah - Maulida Fithria; Dimyati Sajari (Universitas Adiwangsa Jambi, 2023)
This study aims to determine the implementation of the Kahoot application in learning Aqidah Akhlak, the advantages and disadvantages of the Kahoot application free feature, supporting and inhibiting factors in MI Nurul Falah Sindangkarsa. This research method is qualitative descriptive analysis. The subjects of this study were principals, representatives for curriculum, teachers of Aqidah Akhlak and students of class VI. Data collection techniques were do by observation, interviews and documentation. Data analysis is do by reducing data, presenting data and drawing conclusions. The results of this study show that the implementation of the Kahoot application is one of the applications that is effectively used as a learning medium in Aqidah Akhlak subjects through multiple choice and true or false quizzes. The Kahoot application has advantages in terms of free features, namely: it has an attractive appearance, available features, and scoring (evaluation). The disadvantages of the kahoot application free features are: limited use of the free feature, and difficulty reading Arabic multiple choice. Supporting factors in the implementation of the Kahoot application are: the availability of learning tools, teacher skills, and student enthusiasm. Meanwhile, the inhibiting factors are: technical constraints, the capacity of learning devices, overcrowded material, and time constraints.